Empyema Versus Lung Abscess: A Case Report - Steven Imburgio MD; Kameron Tavakolian MD; Anton Mararenko DO; Tasfia Tasnim BS; Taimoor Khan MD; Eric Costanzo DO (SAGE Publishing, 2022)
Lung abscesses and empyemas are 2 forms of pulmonary infection that can present with similar clinical features. However, empyemas are associated with higher morbidity and mortality, necessitating the need to distinguish one from the other. Plain radiographs can sometimes provide clues to help differentiate the 2 pathologies but more often than not, a computed tomography scan is required to confirm the diagnosis. Correct diagnosis is essential, as the goal standard therapeutic intervention for empyemas may be contraindicated in patients with lung abscesses. Empyemas require percutaneous or surgical drainage in combination with antibiotics, while lung abscesses are generally treated with antibiotics alone as drainage can be associated with various complications. We present a case of a 65-year-old man with parapneumonic empyema diagnosed with characteristic findings on chest computed tomography and treated with surgical drainage and antibiotics. We hope to improve patient outcomes by highlighting the classical radiographic findings that help distinguish empyema and abscess.